Comparison of Clinical Data Between Patients With Complications and Without Complications After Spinal Tuberculosis Surgery: A Propensity Score Matching Analysis - Chen, Liyi; Liu, Chong; Ye, Zhen; Chen, Wuhua; Sun, Xuhua; Chen, Jiarui; Li, Hao; Liang, Tuo; Huang, Shengsheng; Jiang, Jie; Chen, Tianyou; Guo, Hao; et al. (Frontiers in Surgery, 2022)
Purpose: This study used a propensity score matching (PSM) analysis to explore the risk factors of postoperative complications and compared the differences in clinical data between them following spinal tuberculosis surgery. Methods: The clinical data of patients with spinal tuberculosis were collected in our hospital from June 2012 to June 2021, including general information, laboratory results, surgical information, and hospitalization costs. The data were divided into two groups: complication and non-complication groups. The baseline data of the two groups were obtained using the PSM analysis. Univariate and multivariate logistic analyses were used to analyze the differences between the two groups. Results: A total of 292 patients were included in the PSM analysis: 146 patients with complications and 146 patients with non-complications. The operation time, incision length, hospital stay, and albumin quantity in the complications group were 162 ±74.1, 11.2 ±4.76, 14.7 ±9.34, and 1.71 ±2.82, respectively, and those in the non-complication group were 138 ±60.5, 10.2 ±3.56, 11.7 ±7.44, and 0.740 ±2.44, respectively. The laboratory costs, examination costs, guardianship costs, oxygen costs, and total costs in the complications group were higher than those in the non-complication group. A significant difference was observed in the albumin quantity by logistic regression analysis (P < 0.05). Conclusion： Several costs in the complication group were higher than in the non-complication group. The albumin quantity may be an independent factor to predict postoperative complications of spinal tuberculosis by logistic regression analysis.